To Live and to Work in Farms, Factories and Workshops. Migrant Women’s Experiences of Illness and Care in Mendoza and Buenos Aires - Linardelli, Maria Florencia; Goldberg, Alejandro (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2018)
In the last decades, there has been an increase in research on female participation in migratory flows. In fact, the research considers that the increase in the number of women involved in the population movements and the visibility of their historical participation configures a process of “feminization of migrations”. In this context, the relation between female migrations and health/ disease/care also became relevant for the social sciences. This article proposes a dialogue between two ethnographic study cases located in Argentina: 1) immigrant women who work in agriculture in Mendoza; 2) Bolivian women immigrant workers inserted in textile workshops in Buenos Aires. Through a comparative approach, we explore the conditions in which their migratory trajectories and the life/housing/work modes take place in the society to which they migrated, their narratives of illness and the care strategies they deploy to recover their health.
Keywords: migrant women; health/illness/care; agricultural work; textile workshops